Microbiological profile and antibiotic vulnerability of bacterial isolates from cancer patients - Alghamdi, Saad (Cellular and Molecular Biology, 2021)
The development of multiple types of infections in patients admitted to the oncology ward is quite obvious. The infection accompanying mortality in cancer patients is attributed majorly to bacteria and then to fungi. Infections can be successful if an appropriate antibiotic is used based on the knowledge of their sensitivity pattern as well as commonly occurring bacteria. A retrospective study was designed to assess numerous bacteria isolated from infections in cancer patients reported to oncology centers of tertiary care hospitals in the Makkah region, Saudi Arabia. Total, 678 cancer patients were enrolled during this study. The clinical isolates were obtained from urine, blood, respiratory samples, soft tissues and skin areas. The processing of the samples was done in accordance with the “Standard Microbiology Laboratory Operating Procedures”. The identification of the isolated was done to their species and vulnerability tests were done as per the guidelines of “Clinical Laboratory Standards Institute”. During this study, 300 samples were acquired from both medical and surgical oncology wards and were cultured during the study period. Klebsiella pneumonia, Staphylococcus aureus, Acinetobacter species, Escherichia coli and Pseudomonas aeruginosa were the microbes that were encountered mostly. The resistance against various antibiotics was found to be encountered by Acinetobacter species whereas resistance against fluoroquinolones, cephalosporin and carbapenems was >50%, found to be encountered by K. pneumonia. There was 43.80% resistance was found against methicillin by the Staph. aureus species. This study concludes that an enhanced antibiotic resistance was found by gram-negative bacilli specifically, E. coli, K. pneumonia and Acinetobacter species. The resistance pattern was not found remarkably in gram-positive strains although, MRSA frequency is found to be upsurged.